Reappraisal generation after acquired brain damage: The role of laterality and cognitive control - Salas Riquelme, Christian E.; Turnbull, Oliver H.; Gross, James J. (Frontiers in Psychology, 2014)
In the last decade there has been a growing literature exploring the neuroanatomical and neuropsychological basis of reappraisal. This data suggests that reappraisal tasks activate a set of areas in the left hemisphere, which are commonly associated to language abilities and verbally mediated cognitive control. The main goal of this study was to investigate such hypothesis, by exploring whether subjects with focal damage to the left hemisphere [LH, n=8] were more markedly impaired on a reappraisal generation task than individuals with right hemisphere lesions [RH, n=8], and healthy controls [HC, n=14]. The reappraisal generation task consisted of a set of ten pictures from the IAPS, depicting negative events of different sort. Participants were asked to quickly generate as many positive reinterpretations as possible for each picture. Two scores were derived from this task; reappraisal difficulty and productivity. A second goal was to explore which cognitive control processes were associated to performance on the reappraisal task. For this purpose, participants were assessed on several measures of cognitive control. The results showed that the average amount of seconds used to generate a first reappraisal did not differ between LH and RH groups. However, significant differences were found between patients with brain injury [LH+RH] and HC, thus suggesting that having a brain damage, with disregard of the laterality of the lesion, does have an impact on reappraisal difficulty. In relation to reappraisal productivity, no differences were found across the three groups, suggesting that neurological groups and HC are equally productive when time constraints is not considered. Finally, only two cognitive control processes –inhibition and verbal fluency- were inversely associated to reappraisal difficulty. The results of this study are discussed in relation to the neuroanatomical and neuropsychological basis of reappraisal, and its implications for neuro-rehabilitation.